Satamo Interactive Media to Improve The Sewing Skills for Mentally Disabled Children: A Preliminary Study - Nining Rulif Fitriani; Mohammad Efendi; Ahmad Samawi (Jurnal ORTOPEDAGOGIA, 2025)
This research was motivated by the problems of mildly mentally retarded children at SMALB in the process of learning sewing skills, especially motorbike gloves and it is named Satamo. Children with mild mental retardation find it difficult to remember the stages in the process of sewing motorbike gloves in sequence and they find it difficult to remember abstract things. This research is qualitative research with a preliminary study method. The research subjects were mildly mentally retarded children at SMALB Blitar City. The data collection process was carried out using direct observation techniques. Test the validity of the data using triangulation techniques. Research results are children with mild mental retardation easily forget and find it difficult to remember abstract things in the process of learning to sew motorbike gloves, so children need video tutorial learning media to make it easier for students to learn motorbike glove sewing skills